2013
DOI: 10.1021/jp407322k
|View full text |Cite
|
Sign up to set email alerts
|

Nanocolumnar Germanium Thin Films as a High-Rate Sodium-Ion Battery Anode Material

Abstract: Both nanocolumnar and dense germanium thin films, synthesized by evaporative deposition, were tested as a potential anode material for sodium-ion batteries. The reversible capacity of the nanocolumnar films was found to be 430 mAh/g, which is higher than the theoretical capacity of 369 mAh/g. The nanocolumnar films retained 88% of their initial capacity after 100 cycles at C/5, whereas the dense films began to deteriorate after ∼15 cycles. Additionally, the nanocolumnar films were stable at charge/discharge ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(166 citation statements)
references
References 55 publications
9
156
0
1
Order By: Relevance
“…[ 445 ] Ge is also theoretically predicted not to be capable of storing Na in its crystalline structure; [ 419 ] therefore, most works have focused on amorphous Ge in thin fi lm and nanowire form. [ 419,[446][447][448] The fi rst report of Ge as a NIB anode material indicated that the amorphous Ge thin fi lm delivered a reversible capacity of 350 mA h g −1 for 15 cycles. [ 448 ] A recent work by Kohandehghan et al also experimentally revealed that crystalline Ge exhibits a capacity of less than 20 mA h g −1 (Figure 18 d, top), whereas amorphorized Ge nanowires exhibited a capacity 370 mA h g −1 (Figure 18 d, bottom).…”
Section: Silicon and Germaniummentioning
confidence: 99%
“…[ 445 ] Ge is also theoretically predicted not to be capable of storing Na in its crystalline structure; [ 419 ] therefore, most works have focused on amorphous Ge in thin fi lm and nanowire form. [ 419,[446][447][448] The fi rst report of Ge as a NIB anode material indicated that the amorphous Ge thin fi lm delivered a reversible capacity of 350 mA h g −1 for 15 cycles. [ 448 ] A recent work by Kohandehghan et al also experimentally revealed that crystalline Ge exhibits a capacity of less than 20 mA h g −1 (Figure 18 d, top), whereas amorphorized Ge nanowires exhibited a capacity 370 mA h g −1 (Figure 18 d, bottom).…”
Section: Silicon and Germaniummentioning
confidence: 99%
“…As a result, the anodes retained up to $80% of their original capacity after 300 cycles [453]. These authors have also explored the use of silicon-germanium alloys [446] and pure germanium [454] as anode materials. Germanium is expected to be a suitable material for battery anodes as its high electronic and ionic conductivity should allow for a very high charge/discharge rate.…”
Section: Li-ion Batteriesmentioning
confidence: 99%
“…Thus, by systematically changing the composition of Si (1Àx) Ge x alloy, it was found that the anode's specific capacity decreased and its electronic conductivity and high-rate performance increased with germanium content. Meanwhile, an outstanding result found when using pure germanium OAD thin films in sodium-ion batteries was a high rate of operation at room temperature with this anode material [454]. For an overall view of this work on ion batteries, readers are redirected to a recent review of this group [231], where in addition to summarizing their advances in the fabrication of anodes, they also comment on the use of amorphous OAD TiO 2 films as cathodes (see Ref.…”
Section: Li-ion Batteriesmentioning
confidence: 99%
“…[ 25,64,65 ] Thankfully, the theoretical calculations predicted that the sodium could alloy with germanium (Ge) to form NaGe (Ge + Na + + e − ↔ NaGe), [ 10 ] giving a theoretical capacity of 369 mA h g −1 . Abel et al [ 20 ] synthesized Ge nanocolumnar fi lms by evaporative deposition with a reversible capacity of 430 mA h g −1 . And a 3D Si/Ge nanorods was reported by Yue et al [ 25 ] exhibited excellent electrochemical performance.…”
Section: Materials Characterizationmentioning
confidence: 99%